PENGARUH LEVEL KETINGGIAN AIR TERHADAP SATURATED STEAM PADA CROSS SECTION WATER TUBE BOILER MENGGUNAKAN BAHAN BAKAR GAS DAN SOLAR - Manggala, Agus; ., Fatria; Lestari, Sutini Pujiastuti; Naim, Barokallah Muhammad; Sastama, Nanda (KINETIKA, 2020)
A boiler is a device that serves to heat water to become high pressure and high temperature steam, using heat from the combustion of fuel in the combustion chamber. The growth of the domestic boiler industry will develop with research on boiler technology. One of the parameters of the steam produced is temperature and pressure. It is necessary to have the right water level in the steam production process to get saturated steam which is in accordance with the theory, which is in the range of 150-374ËšC. The results of the research show that the optimal water level is the 4th condition (60%) because it can produce saturated steam according to the pressure target with a constant state in a continuous process using diesel and gas fuel.